2004
DOI: 10.1007/s10151-004-0165-2
|View full text |Cite
|
Sign up to set email alerts
|

Perineal wound closure after abdomino-perineal excision of the rectum

Abstract: Wound infections have a significant impact on the postoperative morbidity after abdomino-perineal rectum resection (APR). However, the technique of perineal wound closure after APR has not been standardised yet. The prospective German multicentre trial "Colorectal Carcinoma (primary tumor)" (study I) enrolled 10 335 patients with rectal cancer over a time period from 1 January 2000 to 31 December 2002. The APR rate was 24.7% (n=2517). Four hundred and forty-five patients (17.6%) developed an infectious complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…This rate is slightly higher than the 17.6% perineal wound infection rate reported by Meyer et al 11 in a multicentric study with 2517 patients who underwent the Miles procedure. However, Heah et al 6 reported a 46% rate, but this percentage is really variable in the literature; in other studies, it is described to be up to 80%.…”
Section: Discussioncontrasting
confidence: 53%
“…This rate is slightly higher than the 17.6% perineal wound infection rate reported by Meyer et al 11 in a multicentric study with 2517 patients who underwent the Miles procedure. However, Heah et al 6 reported a 46% rate, but this percentage is really variable in the literature; in other studies, it is described to be up to 80%.…”
Section: Discussioncontrasting
confidence: 53%
“…Ultralow HP, where transection is performed above the anal canal, has been compared to abdominoperineal excision (APE). The advantages with HP are shorter operating time, less surgical trauma, and avoidance of a perineal wound [4, 5]. The disadvantage with HP is the high proportion (12–32%) of pelvic abscesses and sepsis [2, 5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical technique of perineal wound closure, after APR, depends on the preference of operating surgeon. In a cohort of 2,517 APR patients 445 (17.6%) developed infectious complication of perineal wound 50. A three layer primary closure—muscle, ischio‐rectal and sub‐cutaneous fat and skin 50, reduced the perineal wound infection rate to 5.4%.…”
Section: Risk Factors Of Non‐healing Of Perineal Woundmentioning
confidence: 99%
“…In a cohort of 2,517 APR patients 445 (17.6%) developed infectious complication of perineal wound 50. A three layer primary closure—muscle, ischio‐rectal and sub‐cutaneous fat and skin 50, reduced the perineal wound infection rate to 5.4%. Nilsson et al 51 reported perineal wound infection in 13/35 (37.1%) patients undergoing salvage APR for recurrent or persistent epidermoid carcinoma anal canal.…”
Section: Risk Factors Of Non‐healing Of Perineal Woundmentioning
confidence: 99%